2017
DOI: 10.3390/su9122189
|View full text |Cite
|
Sign up to set email alerts
|

Awe: An Important Emotional Experience in Sustainable Tourism

Abstract: "Awesome" is one of the most highly desirable experiences for tourists. This study investigates how tourists' awe emotion is induced when tourists visit sacred mountains and how the awe experience influences their satisfaction. A survey is administrated at a famous sacred mountain in China-Mount Emei. Results reveal that the awe experience is more elicited by the perceived vastness of natural environment for secular tourists, while is more encouraged by the perceived sanctity of religious ambience for pilgrim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 40 publications
4
67
1
Order By: Relevance
“…Consequently, it is reasonable to conclude that awe can instigate an individual's feeling of connectedness to larger entities, like nature, by inspiring the perception of the small self. Secondly, awe could motivate people to take in new information or enhance people's openness to novel experiences, which has been confirmed to correlate positively with CN [18,25,26]. Since the openness to novel experience could blur the permeable mental boundaries between self and others [27].…”
Section: Awe and The Connectedness To Naturementioning
confidence: 96%
“…Consequently, it is reasonable to conclude that awe can instigate an individual's feeling of connectedness to larger entities, like nature, by inspiring the perception of the small self. Secondly, awe could motivate people to take in new information or enhance people's openness to novel experiences, which has been confirmed to correlate positively with CN [18,25,26]. Since the openness to novel experience could blur the permeable mental boundaries between self and others [27].…”
Section: Awe and The Connectedness To Naturementioning
confidence: 96%
“…Recently scholars have turned their attention to sustainable experiences as a means of obtaining competitive advantages while enhancing destination sustainability and experience value (Chen et al, 2011;Liu et al, 2016;Lu et al, 2017;Poudel & Nyaupane, 2013;Smit & Melissen, 2018). Chen et al (2011) demonstrate the importance of tourist experiences related to sustainability issues and suggest that in the long run, environmental awareness may lead to changes in tourists' travel intentions.…”
Section: Sustainable Experiencesmentioning
confidence: 99%
“…They find that if tourists feel a sense of "novelty" about a tourist destination, it can increase their sustainability experience and further enhance willingness and satisfaction towards sustainable tourism. Lu et al (2017) found that feeling "awesome" is an important emotional experience in sustainable tourism within a mountain destination. Poudel and Nyaupane (2013) found that positive changes in attitude and behaviour indicated that environmental interpretation (e.g.…”
Section: Sustainable Experiencesmentioning
confidence: 99%
See 2 more Smart Citations